2018
DOI: 10.1002/casp.2373
|View full text |Cite
|
Sign up to set email alerts
|

The discursive “othering” of Jews and Muslims in the Britain First solidarity patrol

Abstract: In this paper, critical discursive psychology is used to analyse the Islamophobic discourse by the far‐right party Britain First in its “solidarity patrol” video. Britain First patrolled in Golders Green, North London, to show support for Jewish communities following the ISIS shooting at the kosher supermarket in Paris on January 9, 2015. The Charlie Hebdo shooting and the shooting at the kosher supermarket (as well as other attacks by members of the Islamic State) have led to Muslims being seen as a threat to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 29 publications
(49 reference statements)
0
27
0
Order By: Relevance
“…Burke (2018) identified similar discursive strategies in the discourse of far-right party Britain First, following terrorist attacks in Paris in 2015, restricting their Islamophobic discourse to “Islamic extremism.” This rhetorical device—rejecting Islam as an ideology rather than Muslims as a people—allows far right groups to project an identity as reasonable and rational, and their hostility morally justifiable.…”
Section: The Language Of Discrimination: Definition Contexts and Tamentioning
confidence: 92%
“…Burke (2018) identified similar discursive strategies in the discourse of far-right party Britain First, following terrorist attacks in Paris in 2015, restricting their Islamophobic discourse to “Islamic extremism.” This rhetorical device—rejecting Islam as an ideology rather than Muslims as a people—allows far right groups to project an identity as reasonable and rational, and their hostility morally justifiable.…”
Section: The Language Of Discrimination: Definition Contexts and Tamentioning
confidence: 92%
“…These studies have demonstrated that DP can provide significant contributions to contemporary understanding of political communication. We focused on two studies that analyse political discourse in current contexts: political debates on the European Union, a highly politicised point of debate in the UK, and far‐right discourse, focusing on how politicians achieve discursive ‘othering’ of Muslims in the aftermath of a terrorist attack (see also Burke, ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 426 Internet memes meeting the set criteria were collected (Finland First N = 209; Soldiers of Odin N = 217) from the public Facebook groups administered by the movements (Retrieved from: https://facebook.com/soldiersofodin/; https://facebook.com/Suomi-Ensin). Material was collected by taking screenshots using a scraping application in the web browser (see e.g., Burke, 2018). The material was collected from November 2017 to January 2018 and includes material posted from January 2015 to the collection date, so the research material reflects the time when the extreme movements were gaining attention in the context of the so-called "refugee crisis" in Finland (Wahlbeck, 2019).…”
Section: Methodsmentioning
confidence: 99%